ZHARBY : PLATFORM BERBASIS WEBSITE UNTUK MENINGKATKAN PENJUALAN KAUS - Alia Mega Putri; Wildan Azis; Yohanes Casmadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study develops Zharby, a website-based platform designed to support the digitalization of the garment industry and enhance T-shirt sales. Many SMEs in this sector have yet to fully utilize digital technology, despite digital transformation being crucial for business efficiency. This research analyzes the challenges in garment marketing and sales, explains the concept and functions of Zharby, and provides recommendations for its implementation. The methodology includes STP analysis, system design using ERD and flowcharts, and black-box testing. The findings indicate that Zharby effectively improves marketing, brand visibility, and order and production management. The platform features a product catalog, ordering system, online payment integration, and inventory management, supporting the needs of modern garment businesses.